The Correlation between Self-esteem and Self-diagnosis Behavior Regarding Mental Health among Adolescents at Senior High School X in Jakarta - Hia, Panca Sinar Prapenta; Pasaribu, Jesika (Persatuan Perawat Nasional Indonesia (JPPNI), 2025)
Research objective: Currently, adolescents tend to self-diagnose due to the influence of their environment and a lack of knowledge about mental health. A key driver factor for adolescents to engage in self-diagnosis is that they are still in the stage of understanding self-concept. The purpose of this study was to determine the relationship between self-esteem and self-diagnosis behaviour regarding mental health in adolescents. Method: The research method used was descriptive correlation. The inclusion criteria for this study were students in grades XI and XII at SMA X Jakarta. Data collection was conducted from October to December 2024. The research instruments used were the Rosenberg Self-Esteem Scale, which had a Cronbach's alpha (ɑ=0.86), and the Self-Identification of Having Mental Illness (SELF-I), which had a Cronbach's alpha (ɑ=0.90). Univariate analysis was conducted by processing central tendency data for self-esteem and self-diagnosis, while bivariate analysis was performed using Kendall's tau-b correlation test. Results: The bivariate test showed a significant relationship between self-esteem and self-diagnosis behaviour (p-value 0.001). Discussion: The study's results indicate the importance of adolescents having high self-esteem to reduce the risk of self-diagnosis behavior. Adolescents need to have good self-esteem to maintain mental health in the future. Conclusion: Respondents are advised to increase their mental health awareness, be more discerning when filtering information from unofficial sources to avoid misinformation and seek professional help immediately. Schools need to implement mental health literacy programs that cover the dangers of self-diagnosis and how to access professional help.Keywords: adolescent, mental health, self-diagnosis, self-esteem